Consent of the People Human Dignity Through Freedom and Equality. - Kemp, David (Melbourne University Publishing, 2022)
David Kemp's masterly account of the story of Australian liberalism after Menzies Consent of the People- Human Dignity through Freedom and Equality 1966-2022 explores how Australia's founding Enlightenment ideals were shaped into a unique national liberalism, embodied in liberal democratic institutions, political parties and shared values. Despite intense partisan loyalties, conservative and radical resistance, and a politics of unequal power and influence, inequality was addressed and personal freedom strengthened. This final book in the landmark, five-volume Australian Liberalism series examines the place of liberal ideas in governments from Harold Holt to Scott Morrison. It shows how reform urgency led to the nation's greatest political crisis in 1975, how prime ministers Fraser and Hawke struggled to manage an economy dominated by powerful union, business and global interests, how during twenty-four crucial years Hawke, Keating and Howard led one of the nation's greatest reform eras, and how social reform continued despite the leadership instability of the post-Howard era. David Kemp assesses political parties as the instruments of reform, and the difficulties of achieving reform in the public interest, highlighting the dangers of factionalism and loss of purpose. He examines how an international revival of liberal thought and rising levels of education revolutionised Australian society and politics, creating a moral-and moralistic-ruling class. In a remarkable half-century Australians strove, with growing success, to achieve their dreams.